Episcopus, presbyter, sacerdos, diaconus: niektóre wyjaśnienia papieża Innocentego I w Liście do Decencjusza, biskupa Gubbio - Turek, Waldemar (Vox Patrum, 2018)
In his Letter to Decentius, Bishop of Gubbio, Pope Innocent I discusses some liturgical questions and specifies the competences of the representatives of the clergy of the time in this regard. First of all, however, he demonstrates the particular link of the community of Rome with the figure of St Peter, which gives rise to the very special role of the Bishop of Rome in relation to other communities, especially in the West. He then concentrates especially on the duties and rights of bishops (episcopi), the principal shepherds and administrators of the divine gifts; on the basis of Sacred Scripture and Tradition he places them at the head of the ecclesiastical hierarchy. Presbyters (presbyteri) are then considered; to them the author of the Letter attributes a significant role especially in teaching and in the celebration of the Eucharist and Baptism. Confirmation is celebrated by the bishop; presbyters, even though they are priests (sacerdotes), do not possess the fullness of the priesthood. The term sacerdos is usually used in reference to bishops and presbyters; however, at times it is reserved to bishops, as, for example, in the discussion on the theme of the beginning of public penance and the admission of the repentant Christian to the community on Holy Thursday.